E-health for the self-care of patients with risk factors associated with the metabolic syndrome - Vélez Álvarez, Consuelo; Vidarte Claros, José Armando; Álvarez Rosero, Rosa Elvira; García Navarro, Jully Andrea (Universidad y Salud, 2016)
The purpose of this review is to identify the scientific evidence on the use of electronic health strategies in interventions aimed at improving self-care of patients with cardiovascular risk factors associated with the presence of metabolic syndrome. The articles analyzed were identified in the databases PubMed, Science Direct, Embase, Elsevier and Scielo. In addition, statistical publications from the World Health Organization, the International Diabetes Federation, Metabolic Syndrome Guide 2009 and ICT Facts and Figures World in 2013 were reviewed. 51 publications between the years 2009 and 2015 were considered, where there were more information about the intervention based on the control of overweight and obesity as a major risk factor for the development of the metabolic syndrome. The evidence found in the scientific literature shows the usefulness of e-health in the management of cardiovascular risk factors associated with metabolic syndrome, and its impact on the quality of life when they are applied with a suitable protocol.